School Theatre between the Pupil’s Awareness and the Ambition of Performance - Bouchelaleg, Hakima (Technium Social Sciences Journal, 2022)
The article talks about the educational theater in schools, pupils have ambitions and great desire to roleplay, because they get this desire by nature.Theater is considered as a father of all arts, which contributes to the development of child’s brain during his early stages of life. However, the educational curriculum failed to include theater as a school subject; on the one hand, cultural centers and other bodies strive to create a theater space that match with the little child’s mind. Therefore, authors should deal with child’s intellectual and imaginative level. Among the examples of child’s love for theater is his simulation and imitation to his teacher when delivering courses in the classroom, he indeed loves and is inclined to act.